Age 6-9 Years: Nutritional Status on Children's Physical Fitness - Sapika Sapika; Rasyidah Jalil; Wahyuni Ulpi; Nurwahidin Hakim (JUARA : Jurnal Olahraga, 2023)
This study aimed to determine whether there is a relationship between children's nutritional status and physical fitness. This research is quantitative research with a correlational design whose goal is to link two or more variables. The instrument used to measure the nutritional status of children is the maximum physical fitness index (BMI) and the Indonesian physical fitness test (TKJI). The results of the data were analyzed using the SPSS application. The results of the descriptive analysis of the nutrition variable had the lowest score of 13.3 and the highest score of 19.2, with an average value of 18.8. In contrast, the TKJI variable had the lowest score of 13 and the highest score of 19, with an average value of 1.9. From the research data and analysis, the significant value is 0.002 <0.05. Thus, it means a relationship between nutritional status and physical fitness with the meaning of H¹ received.